Investigating the effectiveness of managers through an analysis of stakeholder perceptions - Fraser, Campbell; Zarkada, Anna K. (My University, 2003)
Contemporary management thinking is paying a great deal of attention to stakeholder theory which posits that sustainable success rests, to a great extent, with a systematic consideration of the needs and goals of all key stakeholders. This paper examines managerial effectiveness under the light of stakeholder theory. Using multivariate analysis, it investigates perceptions of importance of the dimensions of their effectiveness held by the site managers running 61 high-rise residential construction projects and 268 key project stakeholders. The views were collected through a non-results-based performance measurement tool. The findings of the research show that perceptions of the importance of each one of the performance elements vary significantly across professional groups. Opinions of high performing managers also differ form those of low-performing ones. The application of the method presented in this paper can provide a framework for improvement of both managerial performance and stakeholder relationships.
Keywords: Management effectiveness; Performance measurement (quality); Stakeholders